Monoclonal antibody production: media optimization for enhancement the cell viability of hybridoma cell - Mel, Maizirwan; Mat Saad, Maizura; Hashim, Yumi Zuhanis Has-Yun; Mohamed Salleh, Moharnad Ramlan (Asian Network for Scientific Information, 2008)
Media optimization of RCI hybridoma cell culture for monoclonal antibody production was carried out in T -Flask experiment. The three identified important variables to affect the cell viability were studied. By using Central Composite Design of Response Surface Methodology(STATISTICA v 6.1) has shown that cell viability was mainly affected by glutamine, serum and NaC03 concentration, respectively. Among the 16 nillS tested, Rllll 11 indicated the best viability of the cell (>80% for five days). The critical values were obtained at 13.5, 1.68 and 0.87% for serum, glutamine and NaC03, respectively. These data were very significant where the p-values obtained for glutamine, serum and NaCO, were 0.000069, 0.003968 and 0.342151 (R' ~ 0.95476 and R Adj. ~ 0.88691), respectively.